(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
There are several potential causes of hypoxia and other types of diseases in newborn babies, including: Babies may experience hypoxia or other health issues if they have difficulty during the birthing process, such as a prolonged labor, umbilical cord complications, or meconium aspiration.